MULTICRITERION ANALYSIS AND CHOOSING OF THE OPTIMAL ROUTING IN AD-HOC NETWORKS - Bezruk, Valeriy; Halchenko, Kyrylo (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2018)
The paper discusses the practical aspects of application of multicriterion approach to solving the problem of an optimal routing for wireless self-organizing networks. As the initial metrics analyzed convergence time, memory overhead, control overhead, time complexity and communication complexity.